Boosting Antioxidant Self-defenses by Grafting Astrocytes Rejuvenates the Aged Microenvironment and Mitigates Nigrostriatal Toxicity in Parkinsonian Brain via an Nrf2-Driven Wnt/β-Catenin Prosurvival Axis - Serapide, Maria Francesca; L’Episcopo, Francesca; Tirolo, Cataldo; Testa, Nunzio; Caniglia, Salvatore; Giachino, Carmela; Marchetti, Bianca (Frontiers in Aging Neuroscience, 2020)
Astrocyte (As) bidirectional dialog with neurons plays a fundamental role in major homeostatic brain functions, particularly providing metabolic support and antioxidant self-defense against reactive oxygen (ROS) and nitrogen species (RNS) via the activation of NF-E2-related factor 2 (Nrf2), a master regulator of oxidative stress. Disruption of As–neuron crosstalk is chiefly involved in neuronal degeneration observed in Parkinson’s disease (PD), the most common movement disorder characterized by the selective degeneration of dopaminergic (DAergic) cell bodies of the substantia nigra (SN) pars compacta (SNpc). Ventral midbrain (VM)-As are recognized to exert an important role in DAergic neuroprotection via the expression of a variety of factors, including wingless-related MMTV integration site 1 (Wnt1), a principal player in DAergic neurogenesis. However, whether As, by themselves, might fulfill the role of chief players in DAergic neurorestoration of aged PD mice is presently unresolved. Here, we used primary postnatal mouse VM-As as a graft source for unilateral transplantation above the SN of aged 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mice after the onset of motor symptoms. Spatio-temporal analyses documented that the engrafted cells promoted: (i) a time-dependent nigrostriatal rescue along with increased high-affinity synaptosomal DA uptake and counteraction of motor deficit, as compared to mock-grafted counterparts; and (ii) a restoration of the impaired microenvironment via upregulation of As antioxidant self-defense through the activation of Nrf2/Wnt/β-catenin signaling, suggesting that grafting As has the potential to switch the SN neurorescue-unfriendly environment to a beneficial antioxidant/anti-inflammatory prosurvival milieu. These findings highlight As-derived factors/mechanisms as the crucial key for successful therapeutic outcomes in PD.